Subcritical assembly with thermonuclear neutron source as device for studies of neutron-physical characteristics of thorium fuel - Arzhannikov A. V.; Anikeev A. V.; Beklemishev A. D.; Ivanov A. A.; Shamanin I. V. Igor Vladimirovich; Dyachenko A. N. Alexander Nikolaevich; Dolmatov O. Yu. Oleg Yurevich (2016, 2016)
Title screen